A rapid, automated approach for quantitation of rotavirus and reovirus infectivity - Iskarpatyoti, Jason A.; Willis, Janet Z.; Guan, John; Ashley Morse, E.; Ikizler, Miné; Denise Wetzel, J.; Dermody, Terence S.; Contractor, Nikhat (Journal of virological methods, 2012)
► Rotavirus and reovirus imager-based assays were compared to microscopy-based assays. ► Inhibition of viral replication was quantified. ► Imager-based assays provide automated data collection. ► Imager-based assays provide a high throughput method for screening anti-viral compounds. Current microscopy-based approaches for immunofluorescence detection of viral infectivity are time consuming and labor intensive and can yield variable results subject to observer bias. To circumvent these problems, we developed a rapid and automated infrared immunofluorescence imager-based infectivity assay for both rotavirus and reovirus that can be used to quantify viral infectivity and infectivity inhibition. For rotavirus, monolayers of MA104 cells were infected with simian strain SA-11 or SA-11 preincubated with rotavirus-specific human IgA. For reovirus, monolayers of either HeLa S3 cells or L929 cells were infected with strains type 1 Lang (T1L), type 3 Dearing (T3D), or either virus preincubated with a serotype-specific neutralizing monoclonal antibody (mAb). Infected cells were fixed and incubated with virus-specific polyclonal antiserum, followed by an infrared fluorescence-conjugated secondary antibody. Well-to-well variation in cell number was normalized using fluorescent reagents that stain fixed cells. Virus-infected cells were detected by scanning plates using an infrared imager, and results were obtained as a percent response of fluorescence intensity relative to a virus-specific standard. An expected dose-dependent inhibition of both SA-11 infectivity with rotavirus-specific human IgA and reovirus infectivity with T1L-specific mAb 5C6 and T3D-specific mAb 9BG5 was observed, confirming the utility of this assay for quantification of viral infectivity and infectivity blockade. The imager-based viral infectivity assay fully automates data collection and provides an important advance in technology for applications such as screening for novel modulators of viral infectivity. This basic platform can be adapted for use with multiple viruses and cell types.